Pemanfaatan Media Popis Dalam Pembelajaran IPAS di Kelas III SDN Sungai Miai 8 - Septiana Devi Puspitasari; Zulfa Huriah Dina Kazimah; Nova Soraya; Aldy Ferdiyansyah; Asniwati, Asniwati; Septiana Devi (Jurnal Cahaya Edukasi, 2025)
The background of this study is the low active participation of students caused by the minimal use of learning media, as well as limited facilities and concrete teaching materials that support social studies learning. This study aims to describe and analyze the use of POPIS (Pop Up Book Interactive Tribe) learning media in improving the activeness and understanding of students in social studies learning for grade III at SDN Sungai Miai 8, Banjarmasin. This study uses a qualitative descriptive method with a case study approach, involving a homeroom teacher and 17 students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed using triangulation and data reduction techniques. The results showed that the use of POPIS media significantly increased enthusiasm, interest in learning, and student interaction during the learning process. This media visualizes the material on the diversity of Indonesian ethnic groups in an interesting and easy-to-understand three-dimensional form. Despite technical constraints such as the small size of the media and excessive student enthusiasm, POPIS media still functions well as an innovative alternative in creating fun and meaningful learning.